Clinical importance of the antibiotic regimen in transrectal ultrasound-guided biopsy: quinolone versus cephalosporin. Issue 1 (December 2016) - Lee, Jung; Lee, Sangchul; Hong, Sung; Byun, Seok-Soo; Lee, Sang
Abstract Background Quinolone is recommended as an antimicrobial prophylaxis to prevent infectious complication after transrectal ultrasound-guided biopsy, but the increased appearance of quinolone-resistant organism has raised concerns about the efficacy of quinolone. The current study was performed to evaluate various clinical factors including antimicrobial regimens associated with infectious complication after transrectal ultrasound-guided prostate biopsy. Methods The medical records of 5215 patients who underwent a multicore transrectal ultrasound-guided prostate biopsy between May 2003 and January 2013 at our institution were reviewed. We analyzed clinical variables including prostate-specific antigen, International Prostate Symptom Score, antimicrobial regimen, prostate size, and number of biopsy cores. Univariate and multivariate logistic regression analyses of infection-related hospitalization after prostate biopsy were performed. Results The mean age and median prostate-specific antigen of the entire cohort were 66 years and 6.4 ng/ml, respectively. Twenty-eight (0.54 %) patients developed an infectious complication after prostate biopsy that required hospitalization. Patients who received prophylactic quinolone showed a higher infectious hospitalization rate than patients who received prophylactic third-generation cephalosporin (1.5 vs. 0.3 %;p < 0.001). Multivariate logistic regression analysis demonstrated that the International Prostate Symptom Score (odds ratio = 3.18, 95 % confidence interval 1.24–8.13, p = 0.016) and the use of third-generation cephalosporin (odds ratio = 0.21, 95 % confidence interval 0.10–0.44, p < 0.001) were independent predictors of infection-related hospitalization after prostate biopsy. Conclusion With the emergence of quinolone-resistant microorganisms, third-generation cephalosporin may effectively reduce the risk of infectious complications after transrectal ultrasound-guided prostate biopsy. Severe lower urinary tract symptoms may also be an independent risk factor for infection-related hospitalization after transrectal ultrasound-guided prostate biopsy.